Diaphyseal Humeral Fractures Treated by Plaster Cast & Dynamic Compression Plate - Syed Karam All Shah, Muhammad Azoem Akhund, Sued All Shah, Zahoor Mehl Soomro , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To assess the results of diaphyseal humeral fractures treated by plaster cast and dynamic compression plate and comparing their results regarding hospital stay, union time and complications. Methods: This cross-sectional study was conducted in Orthopaedic Department of Peoples University of Medical and Health Sciences, Nawabshah, during July 2015 to June 2016. A total of 50 consecutive patients of closed diaphyseal humeral shaft fractures were selected according to inclusion criteria. All the cases were admitted from outpatient department, from Trauma Center and were divided in two equal groups A and B. Group A treated with plaster cast (POP) and group B with dynamic compression plates (DCP). Follow-up was done. Results were tabulated and analyzed software. Results: The mean age was 27.12+ 12 years, with male to female ratio of 5.2:1 in POP group and 3.1:1 in DCP group. Time to achieve union in both groups was recorded. Union time ranges 10 to 24 weeks in both groups. The mean healing time in plating group was 12.3 weeks while in cast it was 14.6 weeks. Complications observed were infection 2(8%) patients in DCP VS 0(0%) patients in POP group, iatrogenic palsy of radial nerve observed in 2(8%) patients in DCP VS 0 (0%) patients in POP group, Non union was seen in 1(4%) patient in OCR VS 4 (16%) patients in POP group, delayed union was present in 1(4%) patient in DCP VS 5(20%) patients in POP group, 1(4%) patient show malunion in DCP VS 6(24%) patients in POP group, stiffness of shoulder joint was observed 3(12%) patients in DCP VS 10(40%) patients in POP group. Conclusion: Fracture shaft of humerus is most common among young males. The rate of complications of DCP is lower than that of POP. DCP is related to low risk ofdelayed union as compared to POP.